Study of the Influence of Heat Treatment on OSB Panels Produced with Eucalyptus Wood in Different Layer Compositions - Sugahara, Estefani [UNESP]; Dias, Andre; Arroyo, Felipe; Christoforo, Andre; Costa, Michelle L. [UNESP]; Botelho, Edson C. [UNESP]; Dias, Alfredo M. P. G.; Campos, Cristiane [UNESP] (MDPI, 2022)
In view of the lack of studies aimed at producing and assessing the effects of heat treatment of Oriented Strand Board (OSB) panels, this paper evaluated the thermal degradation kinetics of the raw materials, and the physical and mechanical properties of the panels made with eucalyptus wood and castor oil-based polyurethane adhesive. The OSB panels were subjected to post-production heat treatment (at 175 and 200 °C), replacing the use of wood chemical preservatives. Furthermore, the quantity of materials varied in the face:core:face layers in the proportions of 25:50:25 and 30:40:30, aiming to evaluate the possibility of structural applications for the panels. The results were statistically analyzed and compared with the specifications and classifications for OSB indicated by the European Standard EN 300 and the literature. The application of heat treatment improved the physical properties by decreasing the interaction with water and did not reduce the mechanical properties below the recommended levels. The variation in layer proportions indicated that all of them can be adopted without compromising the panel’s physical-mechanical performance. All treatments are compatible with the EN 300 classification for OSB/4 (heavy duty load-bearing boards for use in humid conditions), presenting technical feasibility and excellent structural profile for civil construction applications.
Keywords: bio-composite; castor oil; Eucalyptus grandis; mechanical properties; physical properties; thermal treatment; wood-products